Diving deep into trouble: the role of foraging strategy and morphology in adapting to a changing environment. Issue 1 (28th December 2020) - Ladds, Monique; Rosen, David; Gerlinsky, Carling; Slip, David; Harcourt, Robert
Abstract : Rapid environmental change may require fur seals and sea lions to make longer or deeper dives to find resources. A systematic review of diving behaviour and physiology revealed that a foraging strategy (epipelagic vs mesopelagic or benthic) was more important in predicting dive behaviour than morphology (fur seal vs sea lion). Abstract: Physiology places constraints on an animal's ability to forage and those unable to adapt to changing conditions may face increased challenges to reproduce and survive. As the global marine environment continues to change, small, air-breathing, endothermic marine predators such as otariids (fur seals and sea lions) and particularly females, who are constrained by central place foraging during breeding, may experience increased difficulties in successfully obtaining adequate food resources. We explored whether physiological limits of female otariids may be innately related to body morphology (fur seals vs sea lions) and/or dictate foraging strategies (epipelagic vs mesopelagic or benthic). We conducted a systematic review of the increased body of literature since the original reviews of Costa et al. (When does physiology limit the foraging behaviour of freely diving mammals? Int Congr Ser 2004;1275 :359–366) and Arnould and Costa (Sea lions in drag, fur seals incognito: insights from the otariid deviants. In Sea Lions of the World Fairbanks . Alaska Sea Grant College Program, Alaska, USA, pp. 309–324, 2006) on behavioural (dive duration and depth) and physiological (total body oxygen stores and diving metabolic rates) parameters. We estimated calculated aerobic dive limit (cADL—estimated duration of aerobic dives) for species and used simulations to predict the proportion of dives that exceeded the cADL. We tested whether body morphology or foraging strategy was the primary predictor of these behavioural and physiological characteristics. We found that the foraging strategy compared to morphology was a better predictor of most parameters, including whether a species was more likely to exceed their cADL during a dive and the ratio of dive time to cADL. This suggests that benthic and mesopelagic divers are more likely to be foraging at their physiological capacity. For species operating near their physiological capacity (regularly exceeding their cADL), the ability to switch strategies is limited as the cost of foraging deeper and longer is disproportionally high, unless it is accompanied by physiological adaptations. It is proposed that some otariids may not have the ability to switch foraging strategies and so be unable adapt to a changing oceanic ecosystem.